The Family as an Agent of Reproduction and Construction of Nyongkolan Culture in the Tanjung Karang Coastal Community - Dwi Hidayati, Nadia; Syafarina, Luckia; Nurhidayati, Nurhidayati; Satria, M.; Rizki Septa, Firda (Journal of Social and Education, 2024)
The Sasak tribe, which almost entirely inhabits the island of Lombok, is a tribe that is strong in preserving their culture and customs, we can find this in the nyongkolan tradition which is still carried out today. This study was studied with the aim of finding out the role of the family in producing and reconstructing the nyongkolan culture which lives as a tradition passed down from generation to generation in the Sasak tribal community. The approach in this study uses an ethnographic approach which is used to holistically understand nyongkolan culture. This research succeeded in finding data that there is an intense role of the family in reproducing and reconstructing the nyongkolan culture in Mataram.